The reminiscence bump in autobiographical memory and for public events: A comparison across different cueing methods. Issue 1 (2nd January 2016) - Koppel, Jonathan; Berntsen, Dorthe
Abstract : The reminiscence bump has been found for both autobiographical memories and memories of public events. However, there have been few comparisons of the bump across each type of event. In the current study, therefore, we compared the bump for autobiographical memories versus the bump for memories of public events. We did so between-subjects, through two cueing methods administered within-subjects, the cue word method and the important memories method . For word-cued memories, we found a similar bump from ages 5 to 19 for both types of memories. However, the bump was more pronounced for autobiographical memories. For most important memories, we found a bump from ages 20 to 29 in autobiographical memory, but little discernible age pattern for public events. Rather, specific public events (e.g., the Fall of the Berlin Wall) dominated recall, producing a chronological distribution characterised by spikes in citations according to the years these events occurred. Follow-up analyses suggested that the bump in most important autobiographical memories was a function of the cultural life script. Our findings did not yield support for any of the dominant existing accounts of the bump as underlying the bump in word-cued memories.